Characterising the attacking patterns of football teams using social networks: players and field zones as network nodes - Freire, L.; Duarte, R.; Marques, P.; Travassos, B. (World Congress of Performance Analysis of Sport IX, 2012)
Recently, social networks analysis has been suggested as a useful tool to capture the complex patterns emerging from the nonlinear interactions between team players (Passos et al., 2011). The aims of this study were: 1) to analyse the strength of interaction between the players within two competing teams 2) to test the field zones as nodes of the networks linked by the ball trajectory dynamics to characterise the attacking playing patterns. Data from pass distribution of two competing teams from the English Premier League, associated to the players and zones of the field, were collected by OPTA. Twelve field zones resultant from four longitudinal and three lateral pitch sections were obtained using a computerised notation system. The origin and end zone of the successful passes formed the links of the network. Data were analysed using Microsoft Excel and SocNetV 0.81 software. Our preliminary analyses showed that the individuals from team A with the highest frequency of connection were the players` number 7, 8, and 10 (Figure 1). Zone 5,7,8 and 9 were the zones that provide larger connectivity with the others (Figure 3). Data allowed identifying the great importance of the central area of the playing field and the midfielders in the development of the attacking patterns in this specific team. In team B, it can be seen that the more frequently connected players were numbers 7 and 11 (Figure 2) and the zone with highest connectivity to the other areas was zone 9, specially with the zones 6 and 12 (Figure 4). Data allowed identifying different trends in the development of the attacking patterns for the two analysed teams. The complementarity between players and field zones as nodes of the networks analyses may be of interest for further investigations in this field.